Hibridasi dan Habitus Pendidikan Islam Tradisional Langgar dalam Masyarakat Madura di Jember, Jawa Timur - Sibilana, Annas Ribab (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
Traditional education is one of the treasures of traditional Islamic education in the archipelago. Langgar was one of the centers of traditional Islamic education in Indonesia before the development of pesantren. This study seeks to present traditional education in the context of Madurese society in Jember. This research was conducted in Langgar Nurul Huda in Kemuning Lor village, Panti District. The research method used is ethnographic, with in-depth interviews with kiai langgar, santri and santri parents. The results showed that the Madurese ethnic community in Jember showed a hybrid society through various cultural expressions in language, symbols, and art. The learning model used in Langgar Nurul Huda seems to provide